Development Canva-based Interactive Learning Multimedia of English Subject for 3rd Grade in Elementary School - Rosa Rahayu Mintarsih; Lovandri Dwanda Putra (Universitas Pendidikan Indonesia (UPI), 2023)
Learning media is a supportive tool in the teaching and learning process. Through learning media, it is hoped that motivation can be provided to students to enhance their interest in learning English material. Interactive learning media can be a solution in selecting the appropriate learning media to present English material in elementary school students. This research aimed: 1) to produce an interactive learning multimedia product based on Canva; 2) to know a product quality by the experts; and 3) to know product effectiveness by teacher and students responses. This RD research employed the Borg and Gall research and development model. However, considering time and resource limitations, it was only tested in one school at SD Muhammadiyah Noyokerten in Yogyakarta with 40 research subjects. Therefore, the execution of this research only extended to the seventh stage. That stage consists of Research and Information Collecting, Planning, Develop Preliminary Form a Product, Preliminary Field Testing, Main Product Revision, Main field Testing, and Operational Product Revision. The last stage is results final product after involved refining the product in the primary field testing. The data analysis techniques used consisted of qualitative and quantitative analyses based on product assessment questionnaire sheets. Based on the research, data was obtained on Canva-based interactive learning multimedia of English subject for 3rd grade in elementary school demonstrates very good quality and is suitable for implementation. This is proven by results of obtained average scores from media expert, material expert, learning expert, teacher, and students of 89,67 get in “Very Good” category.